2012
DOI: 10.1056/nejmoa1110296
|View full text |Cite|
|
Sign up to set email alerts
|

A Mutation in the Thyroid Hormone Receptor Alpha Gene

Abstract: Sum m a r yThyroid hormones exert their effects through alpha (TRα1) and beta (TRβ1 and TRβ2) receptors. Here we describe a child with classic features of hypothyroidism (growth retardation, developmental retardation, skeletal dysplasia, and severe constipation) but only borderline-abnormal thyroid hormone levels. Using wholeexome sequencing, we identified a de novo heterozygous nonsense mutation in a gene encoding thyroid hormone receptor alpha (THRA) and generating a mutant protein that inhibits wild-type re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
306
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(333 citation statements)
references
References 23 publications
17
306
1
3
Order By: Relevance
“…The hypotension observed in the recently identified patient with a mutant thyroid hormone receptor α1 (TRα1) allele (14) prompted us to investigate blood pressure and associated serum parameters in our Thra1 +/m animal model. Surprisingly, despite strongly reduced pulmonary angiotensin-converting enzyme (Ace) expression and lower serum angiotensin II levels in the mutant animals ( Figure 1A), we found that blood pressure was similar to that in wild-type controls ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypotension observed in the recently identified patient with a mutant thyroid hormone receptor α1 (TRα1) allele (14) prompted us to investigate blood pressure and associated serum parameters in our Thra1 +/m animal model. Surprisingly, despite strongly reduced pulmonary angiotensin-converting enzyme (Ace) expression and lower serum angiotensin II levels in the mutant animals ( Figure 1A), we found that blood pressure was similar to that in wild-type controls ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Several types of patients with genetic defects in thyroid hormone signaling have been identified during the past decade, including those with mutations in thyroid hormone transporters (38) and receptors (14,39). In mice and humans, these defects often result in strongly impaired brain function.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of these human mutations further support the genetic evidence. Both the E403× TRα1 mutant described by Bochukova et al (10) and the E397fs406× TRα1 mutant described by van Mullem et al (11) act in a dominant negative fashion to interfere with the transcription activity of WT TRs. In vitro studies further show that the E403× TRα1 mutant is defective in its ability to release corepressors in the presence of T3 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also shown that mutations of the Thra gene in mice lead to phenotypes distinct from those of mice with knockin mutations of the Thrb gene (7)(8)(9). However, these mouse genetic findings showing that mutations of the Thra gene are not embryonic lethal, but have phenotypes differ from mutations of the Thrb gene, were not verified in humans until recently when patients were found with mutations of the THRA gene (10,11). Indeed, TRα1PV shares the same mutated C-terminal sequence (-TLPRGL) with truncated termination at amino acid L406 as those of two patients with frameshift mutations of the THRA gene (11).…”
mentioning
confidence: 99%
“…By contrast, genetic data indicate that the two receptors have very different functions in vivo. Two germ-line mutations have been reported recently for the human Thra gene (14,15). The patients share typical symptoms of congenital hypothyroidism, including cognitive impairments.…”
mentioning
confidence: 99%